Development of bentonite-based organo-geopolymer hybrid wood binder - Gonultas, Oktay (Springer, 2024)
The study addresses concerns associated with formaldehyde-based adhesives in wood panel board production by proposing geopolymer-based wood binders as promising, formaldehyde-free alternatives. Using bentonite, the research delves into the development and performance properties of this geopolymer wood binder. The BET method was employed for the surface characterization of precursor raw materials for binder preparation. Si and Al elements identified through XRF analysis were correlated with characteristic bands in the FTIR spectrum. Alkaline activation solutions, employing sodium silicate and sodium hydroxide with a molar ratio range of 0.5 to 2.5 (SiO2:Na2O), revealed that binders with a molar ratio of 2.5 exhibited lower pH and higher adhesion strength. Different geopolymer formulations at solution to powder ratios (s/p) of 1.33, 3, and 3.5 determined s/p 3.5 as optimal for bentonite-based organo-geopolymer binders. Viscosity, gel time, pH, and solids content were examined, showing the effectiveness of substituting 10% silica fume to enhance the geopolymerization process and improve adhesion. Modifications using citric acid, sucrose, paraffin, pMDI, triacetin, and resorcinol demonstrated wet bonding strength comparable to urea formaldehyde adhesive. Analytical techniques, including FTIR spectroscopy, XRD analysis, and SEM EDX analysis, provided insights into functional groups, crystallographic properties, and microstructural characteristics. The concentration of Si and Al compounds on the bonding line, coupled with Na element diffusion, was observed through these analyses. Light microscopy of lap shear samples revealed a thinner bonding line, affirming effective binder penetration into wood cell lumens in bentonite-based organo-geopolymer binder formulations.
Keywords: Mechanical-Properties; Silica Fume; Adhesive; Composite; Ash; Xrd; Ir